PENGHAPUSAN DAN PELAKSANAAN LELANG BARANG MILIK PERSEROAN TERBATAS BANK NEGARA INDONESIA (PERSERO) TBK CABANG YOGYAKARTA - , ririn arini subagyo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is aimed at identifying the obliteration and execution of auction of goods owned by PT Bank Negara Indonesia (Persero) Tbk., Yogyakarta Branch. The research belongs to a juridical-empirical research, that is a research based on the field research in order to obtain primary data. Library research was conducted to obtain secondary data so as to support and complete the existing data. The primary data were obtained through the field research by interviewing and distributing questionnaires, while the secondary data were obtained from primary, secondary and tertiary law materials through the library research. This research employed nonrandom sampling method, which did not give equal chance for each population to be selected as the samples, while the sampling applied purposive sampling method. The research result indicated that the implementation of obliterating goods owned by PT Bank Negara Indonesia (Persero) Tbk Yogyakarta Branch applies its own regulation. The prevailing regulation is the Corporate Governance Book Number IN/PP/001/UMM dated on March 18, 2010. The obliteration is performed through the following stages